P16/ki67 and E6/E7 mRNA Accuracy and Prognostic Value in Triaging HPV DNA-Positive Women. (3rd August 2020) - Giorgi Rossi, Paolo; Carozzi, Francesca; Ronco, Guglielmo; Allia, Elena; Bisanzi, Simonetta; Gillio-Tos, Anna; De Marco, Laura; Rizzolo, Raffaella; Gustinucci, Daniela; Del Mistro, Annarosa; Frayle, Helena; Confortini, Massimo; et al.
Abstract: Background: The study presents cross-sectional accuracy of E6 and E7 (E6/E7) mRNA detection and p16/ki67 dual staining, alone or in combination with cytology and human papillomavirus (HPV)16/18 genotyping, as a triage test in HPV DNA-positive women and their impact on cervical intraepithelial neoplasia (CIN2+) overdiagnosis. Methods: Women aged 25-64 years were recruited. HPV DNA-positive women were triaged with cytology and tested for E6/E7 mRNA and p16/ki67. Cytology positive women were referred to colposcopy, and negatives were randomly assigned to immediate colposcopy or to 1-year HPV retesting. Lesions found within 24 months since recruitment were included. All P values were 2-sided. Results: 40 509 women were recruited, and 3147 (7.8%) tested HPV DNA positive; 174 CIN2+ were found: sensitivity was 61.0% (95% confidence interval [CI] = 53.6 to 68.0), 94.4% (95% CI = 89.1 to 97.3), and 75.2% (95% CI = 68.1 to 81.6) for cytology, E6/E7 mRNA, and p16/ki67, respectively. Immediate referral was 25.6%, 66.8%, and 28.3%, respectively. Overall referral was 65.3%, 78.3%, and 63.3%, respectively. Cytology or p16/ki67, when combined with HPV16/18 typing, reached higher sensitivity with a small impact on referral. Among the 2306 HPV DNA-positive and cytology-negative women, relative CIN2+ detection in those randomly assigned at 1-year retesting vs immediate colposcopy suggests a -28% CIN2+ regression (95% CI = -57% to +20%); regression was higher in E6/E7 mRNA-negatives (Pinteraction = .29). HPV clearance at 1 year in E6/E7 mRNA and in p16/ki67 negative women was about 2 times higher than in positive women ( P interaction < .001 for both). Conclusions: p16/ki67 showed good performance as a triage test. E6/E7 mRNA showed the highest sensitivity, at the price of too high a positivity rate to be efficient for triage. However, when negative, it showed a good prognostic value for clearance and CIN2+ regression.